2013
DOI: 10.1021/nl401849t
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion/Fragmentation of Layered Composite Cathode and Related Capacity/Voltage Fading during Cycling Process

Abstract: The Li-rich, Mn-rich (LMR) layered structure materials exhibit very high discharge capacities exceeding 250 mAh g(-1) and are very promising cathodes to be used in lithium ion batteries. However, significant barriers, such as voltage fade and low rate capability, still need to be overcome before the practical applications of these materials. A detailed study of the voltage/capacity fading mechanism will be beneficial for further tailoring the electrode structure and thus improving the electrochemical performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
312
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(326 citation statements)
references
References 33 publications
8
312
1
1
Order By: Relevance
“…Previous studies have attributed the surface reduced layer mainly to electrochemical processes with little attention dedicated to the effects of electrode-electrolyte reactivity 4,5,17 . Here we found that a surface reduced layer similar to the ones observed during high-voltage cycling is also created after an NMC electrode was immersed in the electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have attributed the surface reduced layer mainly to electrochemical processes with little attention dedicated to the effects of electrode-electrolyte reactivity 4,5,17 . Here we found that a surface reduced layer similar to the ones observed during high-voltage cycling is also created after an NMC electrode was immersed in the electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structural and/or chemical rearrangements at surfaces determine the way a material interacts with its surrounding environment, thus controlling the functionalities of the material [6][7][8][9][10] . Specifically, the surfaces of lithium-ion battery electrodes evolve simultaneously with charge-discharge cycling (that is, in situ surface reconstruction and formation of a surface reaction layer (SRL)) that can lead to deterioration of performance 4,5,11 . An improved understanding of in situ surface reconstruction phenomena imparts knowledge not only for understanding degradation mechanisms for battery electrodes but also to provide insights into the surface functionalization for enhanced cyclability 12,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three main reduction processes (which accompany Li-intercalation) can be identified: Re1 at about 4.5 V is related to Li occupation in the tetrahedral sites; Re2 at 3.7 V can be ascribed to Li occupation in the octahedral sites corresponding to Ni 4+ /Ni 2+ and Co 4+ /Co 3+ ; and Re3 at <3.5 V can be explained by Li occupation in the octahedral sites associated with Mn 4+ /Mn 3+ redox [83,84]. Further delithiation beyond 4.5 V during the first cycle leads to oxygen vacancies and the subsequent migration of transition metal ions into lithium sites and lithium ions into tetrahedral sites, resulting in a distorted oxygen lattice [85][86][87][88]. Figure 11B,D shows that all the reduction peaks shift with cycling, but the shifting is more serious for 0.5Li 2 migration of transition metal ions into lithium sites and lithium ions into tetrahedral sites, resulting in a distorted oxygen lattice [85][86][87][88].…”
Section: Porous Li-and Mn-rich High-energy-density Cathode Materialsmentioning
confidence: 99%
“…To overcome this problem, many studies have focused on stabilizing the structure with various efforts, such as surface modifications and transition‐metal‐ion substitutions,2, 5, 6, 7, 8 but none of the efforts could completely eliminate the phase transition. In this regard, new approaches are needed to develop high‐capacity cathodes.…”
Section: Introductionmentioning
confidence: 99%